1982
DOI: 10.2466/pms.1982.55.1.307
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of Response Style across Types of Response Formats

Abstract: Effects of response style on various commonly used fixed-response formats are examined. Data suggest that Likert-type formats are relatively consistently affected by response style regardless of the number of categories in the format. Non-anchored numbers were less affected by stylistic responses, while linear formats and various forms of human faces are the most problematic. Across types, strongest correlations were obtained for the various forms of linear formats and human faces making their use problematic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Bardo & Yeager, 1982;DeVellis, 2003). Normative section was split into three 20-or 21-item batteries joined by a repeated thematic phrase in the beginning.…”
Section: Norms Measuresmentioning
confidence: 94%
“…Bardo & Yeager, 1982;DeVellis, 2003). Normative section was split into three 20-or 21-item batteries joined by a repeated thematic phrase in the beginning.…”
Section: Norms Measuresmentioning
confidence: 94%
“…All sections used 4-point Likert rating scales. Pretest work in the u s a and in the Ukraine using a number of scales showed that this format gave the best results in terms of interpretability of the ensuing factorial structure (cf., Bardo & Yeager, 1982;DeVellis, 2003). The Swedish instrument was pretested with a sample of 46 individuals; the American instrument had no pretests.…”
Section: Don't Know About Others But For Me X Is: Not Important Ofmentioning
confidence: 94%
“…Pretest work in the USA and in the Ukraine using a number of scales showed that this format gave the best results (cf., Bardo and Yeager, 1982;DeVellis, 2003). All sections used 4-point Likert rating scales.…”
Section: Values and Norms Measuresmentioning
confidence: 94%